Respuestas
Respuesta dada por:
1
(2a+8b)²
4a²+32ab+64b²
4a²+32ab+64b²
jonathan3054:
hay mas no?
Respuesta dada por:
7
Resolver.
Aplicas productos notables.
(a + b)² = a² + 2ab + b²
(2a + 8b)² =
(2a)² + 2(2a)(8b + (8b)² =
2²a² + 32ab + 8²b² =
4a² + 32ab + 64b²
Respuesta.
4a² + 32ab + 64b²
Aplicas productos notables.
(a + b)² = a² + 2ab + b²
(2a + 8b)² =
(2a)² + 2(2a)(8b + (8b)² =
2²a² + 32ab + 8²b² =
4a² + 32ab + 64b²
Respuesta.
4a² + 32ab + 64b²
Preguntas similares
hace 7 años
hace 7 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años